Drained‐to‐undrained transition of bulk modulus in fluid‐saturated porous rock induced by dead volume variation. (15th July 2020) - Tan, Wenhui; Müller, Tobias M.; Ba, Jing; Mikhaltsevitch, Vassily; Cao, Chenghao
ABSTRACT: We examine the effect of poroelastic boundary conditions when determining elastic properties of fluid‐saturated porous rocks from forced‐oscillation laboratory experiments. One undesired yet often unavoidable complication in the estimation of the undrained bulk modulus is due to the presence of the so‐called dead volume. It implies that some fluid mass can escape the rock sample under applying a confining pressure perturbation. Thus, the dead volume compromises the undrained state required to unambiguously determine the undrained bulk modulus. In this paper, we model data of recently performed low‐frequency (0.1 Hz) measurements. Therein, the dead volume has been systematically varied from 10% to 1000% of the pore volume. For the smallest dead volume, the inferred bulk modulus is close to the Biot–Gassmann undrained bulk modulus. With increasing dead volume, the experimentally inferred bulk modulus approaches the drained bulk modulus. We show that the transition from undrained to drained state as a function of dead volume can be modelled with a 1D poroelastic model for the rock sample‐dead volume system with a boundary condition that honours the continuity of the fluid volume flux. We discuss the limitations of the 1D model when applied to data recorded at higher frequencies (up to 100 Hz).